Update on integration development within the Caribbean Community and the effect on other trade relationships in the hemisphere; and, trade liberalisation and the challenge of open regionalism - Carrington, Edwin W. ([CCS] GeorgetownGY, 1992)
Provides an update on integration developments within CARICOM and makes some comments on trade liberalisation and the challenge of open regionalism.